NEW OSAZONE DIAGRAM FOR DETERMINATION OF TWO ALDOSES AND A KETOSE THAT FORM IDENTICAL OSAZONE (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
A new and interesting osazone diagram was presented for determination and identification of a pair aldoses and a ketose that makes the same osazone. This chart facilitated the finding any aldose and/or ketose yielded the same osazone.